Dead man's deal - Drake, Jocelynn (Asylum tales, 2013)
Wizard and tattoo artist Gage escaped the dread Ivory Towers, but no one can outrun his past forever. The wizards know Gage is using forbidden magic, and they will stop at nothing - even destroying cities - to stop him...and the nascent human uprising.